Structural Analysis of Healing Tourism Experiences and Their Impact on Revisit Intentions Within the Multidimensional Wellness Tourism Framework Based on Local Wisdom - Lastiani Warih Wulandari (Glosains: Jurnal Sains Global Indonesia, 2026)
Background: Despite the growth of wellness tourism, few studies have empirically examined healing as a multidimensional construct within the Hybrid Wellness Tourism model, integrating traditional, modern, and digital practices. The distinction between wellness tourism, healing tourism, and Hybrid Wellness Tourism remains underexplored, particularly in the context of Indonesian local wisdom. Objective: This study aims to empirically validate a multidimensional healing construct within the Hybrid Wellness Tourism framework, examining its impact on revisit intentions at local wisdom-based wellness destinations in Indonesia. Methods: An explanatory quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM) was employed. Data were collected from 312 wellness tourism participants in Java, Indonesia, utilizing structured questionnaires and focusing on four dimensions of healing experiences: Anticipated, Embodied, Interactive, and Reminiscence Healing. Results: The findings show that Healing Tourism Experience significantly influences revisit intentions, with an R² of 0.64. Embodied Healing (β = 0.34) and Reminiscence Healing (β = 0.29) had the strongest effects, followed by Interactive (β = 0.18) and Anticipated Healing (β = 0.14). The Hybrid Wellness Tourism framework, integrating traditional, modern, and digital elements, proved to be a strong predictor of destination loyalty. Conclusion: This study expands wellness tourism literature by validating a multidimensional second-order healing construct. It highlights the importance of physical, emotional, and post-trip reflective experiences in fostering tourist loyalty, offering practical implications for destination managers to design immersive wellness experiences, integrate digital technologies, and involve local communities to enhance sustainability and revisit intentions.